Sporidesmiella dulongjiangensis sp. nov., a new lignicolous freshwater fungus from Dulongjiang River in Yunnan Province, China - Wen, Li-Qun; Wang, Ying; Shen, Hong-Wei; Yang, Lin; Li, Yun-Xia; Luo, Zong-Long (Phytotaxa, 2026)
During a survey of lignicolous freshwater fungi from the Dulongjiang River in Yunnan Province, China, a hyphomycetous fungus was collected from submerged decaying wood. Based on morphological characteristics and phylogenetic analysis of combined ITS, LSU, tef1-α and rpb2 sequence data, a new species, Sporidesmiella dulongjiangensis is introduced. The species is characterized by macronematous, unbranched, septate conidiophores; monoblastic, integrated, terminal, conidiogenous cells with percurrent proliferations; and acropleurogenous, clavate or obovoid, distoseptate, guttulate conidia. Detailed description and illustrations of the new species are provided, along with a morphological comparison with phylogenetically related taxa.